Analisis Faktor-Faktor yang Mempengaruhi Adopsi Teknologi Artificial Intelligence oleh Mahasiswa Akuntansi di Kota Batam - Grace Grace; Ni Putu Winda Ayuningtyas (CV. Ulil Albab Corp, 2024)
Artificial Intelligence advancements are revolutionizing business, particularly in accounting, offering transformative potential in data management and decision-making. As the demand for accounting skills in business evolves, adopting AI becomes vital for maintaining professional relevance in the digital age. The aim of this study is to examine the effect of technology readiness, perceived usefulness, and perceived ease of use on the adoption of artificial technology by accounting students. This study uses quantitative methods using a questionnaire with 30 items. The data of this study was collected through a questionnaire filled by 152 active accounting students in Batam City, Indonesia, who had completed computerized accounting courses during the academic year of 2023-2024. This study conducted the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach to analyze the collected data. The findings show that perceived ease of use significantly impacts perceived usefulness and the adoption of artificial intelligence technology. Additionally, technology readiness has been shown to influence both perceived usefulness and perceived ease of use. However, it was found that neither technology readiness nor perceived usefulness affects the adoption of artificial intelligence technology. The result of the study suggests.